2003
DOI: 10.1128/iai.71.12.6871-6883.2003
|View full text |Cite
|
Sign up to set email alerts
|

TheMycobacterium tuberculosisComplex-Restricted Genecfp32Encodes an Expressed Protein That Is Detectable inTuberculosis Patients and Is Positively Correlated with PulmonaryInterleukin-10

Abstract: Human tuberculosis (TB) is caused by the bacillus Mycobacterium tuberculosis, a subspecies of the M. tuberculosis complex (MTC) of mycobacteria. Postgenomic dissection of the M. tuberculosis proteome is ongoing and critical to furthering our understanding of factors mediating M. tuberculosis pathobiology. Towards this end, a 32-kDa putative glyoxalase in the culture filtrate (CF) of growing M. tuberculosis (originally annotated as Rv0577 and hereafter designated CFP32) was identified, cloned, and characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 76 publications
4
65
1
Order By: Relevance
“…The percentages of cell types obtained by induced sputum in the current study also appeared similar to those in our previous study using BAL cells (18). In addition, we previously observed that levels of IL-10 protein in induced sputum samples of pulmonary TB patients positively correlated with the amount of CFP32, a M. tuberculosis Ag, indicating that IL-10 levels correlate with the failure of immune control M. tuberculosis (37). In the current study, using lung cells from induced sputum we confirmed and further extended our prior results (18,37); TB cases expressed significantly higher levels of mediators associated with Th1-like immunity (IFN-␥, IL-12p35, IL-12p40, and NEMO) compared with patients with OLD or with clinically well HCW.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The percentages of cell types obtained by induced sputum in the current study also appeared similar to those in our previous study using BAL cells (18). In addition, we previously observed that levels of IL-10 protein in induced sputum samples of pulmonary TB patients positively correlated with the amount of CFP32, a M. tuberculosis Ag, indicating that IL-10 levels correlate with the failure of immune control M. tuberculosis (37). In the current study, using lung cells from induced sputum we confirmed and further extended our prior results (18,37); TB cases expressed significantly higher levels of mediators associated with Th1-like immunity (IFN-␥, IL-12p35, IL-12p40, and NEMO) compared with patients with OLD or with clinically well HCW.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we previously observed that levels of IL-10 protein in induced sputum samples of pulmonary TB patients positively correlated with the amount of CFP32, a M. tuberculosis Ag, indicating that IL-10 levels correlate with the failure of immune control M. tuberculosis (37). In the current study, using lung cells from induced sputum we confirmed and further extended our prior results (18,37); TB cases expressed significantly higher levels of mediators associated with Th1-like immunity (IFN-␥, IL-12p35, IL-12p40, and NEMO) compared with patients with OLD or with clinically well HCW. Our observations are supported by other studies that measured IFN-␥, TNF-␣, or IL-12 (41,43) and by microarray evaluation of BAL cells from TB patients (8,44).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…M. bovis was identified from the results of the multiplex-PCR, which targets three genetic regions that are cfp32, RD9 and RD12. 6,[22][23][24] In summary, our study clearly provides evidence that the LAMP assay is a method that allows direct detection of MTC from processed clinical/abattoir specimens. This means that the technique can also be applied in the field of veterinary medicine for rapid confirmation of suspected cases.…”
Section: Discussionmentioning
confidence: 56%
“…Recently published studies conducted by our group at the University of Cornell show that one of these proteins, known as CFP32, is expressed only by members of the Mtb complex and is not expressed by other species of mycobacteria. In vitro and ex vivo studies have shown that this protein is able to induce considerable production of IL-10, which, as previously mentioned, facilitates the progress of the infection (7) . The presence of this gene in the mycobacteria has advanced the development of new diagnostic methods as well as aiding the identification of subspecies within the genus, with implications for studies that focus on molecular epidemiology (8) .…”
Section: The Role Of Cytokines In the Development Of Tuberculosismentioning
confidence: 52%